2016
DOI: 10.1016/j.bbmt.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone, Azithromycin, and Montelukast Treatment for New-Onset Bronchiolitis Obliterans Syndrome after Hematopoietic Cell Transplantation

Abstract: Bronchiolitis obliterans syndrome (BOS) after allogeneic hematopoietic cell transplantation (HCT) is associated with high mortality. Purpose: We hypothesized that FAM (inhaled Fluticasone, Azithromycin, and Montelukast) with a brief steroid pulse could avert progression of new-onset BOS. Experimental design: We tested this in a phase II, single-arm, open label, multicenter study (NCT01307462). Results: Thirty-six patients were enrolled within 6 months of BOS diagnosis. The primary endpoint was treatment failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(133 citation statements)
references
References 49 publications
(68 reference statements)
2
128
1
2
Order By: Relevance
“…For the treatment of new-onset BOS after HCT, a study of inhaled fluticasone, azithromycin, and montelukast (FAM) with brief steroid burst (1 mg/kg per day prednisone) and rapid taper has been reported (0.25 mg/kg per week) (Figure 2). 54 This prospective, multi-institutional study of 36 patients showed stabilization or improvement in 94% of patients at 3 months and overall survival of 97% at 6 months. 54 Based on these results, I initiate FAM therapy for all newly diagnosed patients in addition to continuation or resumption of classical cGVHD therapy with calcineurin inhibitor or sirolimus.…”
Section: 305253mentioning
confidence: 99%
See 1 more Smart Citation
“…For the treatment of new-onset BOS after HCT, a study of inhaled fluticasone, azithromycin, and montelukast (FAM) with brief steroid burst (1 mg/kg per day prednisone) and rapid taper has been reported (0.25 mg/kg per week) (Figure 2). 54 This prospective, multi-institutional study of 36 patients showed stabilization or improvement in 94% of patients at 3 months and overall survival of 97% at 6 months. 54 Based on these results, I initiate FAM therapy for all newly diagnosed patients in addition to continuation or resumption of classical cGVHD therapy with calcineurin inhibitor or sirolimus.…”
Section: 305253mentioning
confidence: 99%
“…54 This prospective, multi-institutional study of 36 patients showed stabilization or improvement in 94% of patients at 3 months and overall survival of 97% at 6 months. 54 Based on these results, I initiate FAM therapy for all newly diagnosed patients in addition to continuation or resumption of classical cGVHD therapy with calcineurin inhibitor or sirolimus. The mechanistic rationale for these agents are: inhaled steroids provide local anti-inflammatory effects, azithromycin impairs interleukin-8 (IL-8) production and neutrophilia, and montelukast blocks leukotriene activity, impairing cellular homing and activation and possibly blocking fibroblast proliferation and collagen deposition (Figure 4).…”
Section: 305253mentioning
confidence: 99%
“…Another single-agent, openlabel study evaluated montelukast in 25 patients with established BOS after allogenic hematopoetic stem cell transplantation and showed stabilization with less than 15% decline in FEV1 for the entire cohort over 6 months of treatment [25]. Also in combination therapy (with fluticasone and azithromycin (FAM) or combination with budesonide/formoterol and n-acetylcysteine), montelukast shows improvement of lung function in patients with BOS after allogenic hematopoetic stem cell transplantation [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Norman et al [10] reported a prednisonesparing effect of combination therapy with inhaled fluticasone propionate, AZI, and montelukast (FAM) for a case series of eight HCT-BOS recipients compared to 14 historical controls (inhaled fluticasone and montelukast have also been suggested to have potential treatment benefit for BOS in both HCT and/or LTX recipients on the basis of small case series investigations). Williams et al [11] subsequently reported that FAM therapy for a larger cohort of 36 patients enrolled in a single-arm, open-label, multicenter clinical trial was associated with a significantly reduced likelihood of treatment failure (defined as ≥10% decline in FEV1 at 3 months) for the FAM cohort versus historical controls and allowed a substantial reduction in corticosteroid dosing. Additional multi-center, prospective, randomized, placebo-controlled clinical trials (RCTs) are currently underway to better evaluate the efficacy of AZI for HCT-BOS, but results are not yet available.…”
Section: How Can Bos Be Treated?mentioning
confidence: 99%